Development and Application of a Modified Biochar-Calcium Alginate Composite (MB-CA) for In Situ Remediation of Cadmium-Contaminated Soil - Sijia Sun; Yuying Wang; Yanru Zhang; Lina Wu; Xinyi Wang; Guoyu Wang; Weitao Sun; Dasong Lin; Yajun Wang (Gels)
Agricultural monitoring reveals cadmium (Cd) as the most prevalent heavy metal pollutant in Chinese agricultural soils, with 7.0% of sampled sites exceeding the national soil environmental quality standard (GB 15618-2018), creating substantial risks for crop safety. In situ remediation is a cost-effective method that can modify the speciation and migration properties of Cd in soil. The previous stage of research studies conducted basic characterization of materials and predicted their adsorption capacity in solution environments. This study focuses on the application effects in soil environment. We cross-linked modified biochar and calcium alginate hydrogels to fabricate a composite material (MB-CA) and determined its excellent adsorption performance for cadmium. This study is a continuation of our previous work, focusing on determining the thermodynamic model of adsorption materials, the applicable environment of composite materials, the influence on soil microorganisms, and its effect on the reduction in Cd content in agricultural products. The research found that the adsorption of Cd2+ by MB-CA conforms to the Freundlich isotherm model. MB-CA has the ability to regulate pH, achieving outstanding adsorption capacity at pH 4–6. The effect of MB-CA on lettuce is verified through pot experiment and field experiment. The Cd2+ content in plants decreased by 63.11% and 76.92%, respectively. Additionally, MB-CA did not negatively impact microbial abundance. This study further discussed the performance and application effect of MB-CA, providing new solutions for soil remediation.